The enforced disappearance and its effects in the novel Meu pai, acabaram com ele, by Luiz Claudio Cardoso - Franco Junior, Arnaldo [UNESP] (Univ Federal Santa Maria, 2023)
In this article, I analyze and interpret the novel Meu pai, acabaram com ele, by Luiz Claudio Cardoso, which talks about the enforced disappearance and its effects on the missing person's family and inner social circle. Referring to a real fact of life - the enforced disappearance of a Brazilian deputy, Rubens Paiva, in the 1970's - the novel fictionalizes that fact and explores, dramatically, the impact that violence and the state terrorism have on the ones who, surviving that kind of catastrophe, have to deal with the perplexities and anguish stemming from the process of loss that never ends and deploys them on the threshold between mourning and the impossibility of its fulfillment.
Keywords: Enforced disappearance; Narrative; State terrorism